ҚУЁШ БАТАРЕЯЛАРНИ ПАРАМЕТРЛАРИ ЎЛЧАШ УЧУН КИЧИК ЎЛЧАМЛИ ҚУЁШ СИМУЛЯТОРИНИНГ НУРЛАНИШ ХАРАКТЕРИСТИКАСИ - Насруллаев, Юсуф (Innovatsion texnologiyalar, 2022)
Solar simulators with one or more light sources (portholes) are used for solar cell testing. Analysis of the experimental data showed that the effect of light absorption is opposite to the effect of reverse bias and can almost completely compensate for it over time. The main goal is to ensure a uniform and stable distribution of radiation from a set of ten halogen lamps measuring 15x25 sm. The lamps are placed perpendicular to each other on a flat surface. The halogen lamps of the same type are described and the total illumination of the sun simulator through a 2x5 grating is measured. The results showed that the location of luminaires capable of reaching 1000 W/m2 is located on an area of 100x150 m2.